The perception of public towards corruption among public servants / Kennedy Lansu and Nur Farida Sukandar - Lansu, Kennedy; Sukandar, Nur Farida (2015)
The corruption among the public servants have been became a wide issue that influence the perception of the public towards the government. The research on the perception of public was conducted to explore the relationship between the influence of media, the job environment and the level of position whether it lead to the corruption among the public servants in the government. The objective of the research is about to study the perception of public towards corruption among public servants and also to determine the factors that associated about the perception of public towards corruption among public servants. The research method for this study is based on the quantitative methods. Self-administers questionnaire will be used as the instruments in data collection. In our research, the sample is the public from the area of Tuaran, Sabah. In our findings, we have find out that there are significant correlation between the perception and the factors that influence the perception towards the corruption among the public servants.